2015
DOI: 10.18632/oncotarget.3710
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of xCT-mediated regulatory network: identification of novel targets against AIDS-associated lymphoma

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) is the etiological agent of primary effusion lymphoma (PEL), a rapidly progressing malignancy mostly arising in HIV-infected patients. Even under conventional chemotherapy, PEL continues to portend nearly 100% mortality within several months, which urgently requires novel therapeutic strategies. We have previously demonstrated that targeting xCT, an amino acid transporter for cystine/glutamate exchange, induces significant PEL cell apoptosis through regulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…1 . Enrichment analysis shows that several major cellular functions were affected within SASP-treated PEL cells, including oxidative stress/antioxidant defense system, apoptosis/anti-apoptosis/cell death, and cellular response to unfolded proteins/topologically incorrect proteins, which is consistent with the SASP-induced apoptosis phenotype that we recently observed in KSHV + PEL cell-lines [2] , [3] . Therefore, our microarray data indicate that xCT as well as downstream controlled genes may represent new “drug targets” for better PEL treatment.…”
Section: Experimental Design Materials and Methodssupporting
confidence: 85%
“…1 . Enrichment analysis shows that several major cellular functions were affected within SASP-treated PEL cells, including oxidative stress/antioxidant defense system, apoptosis/anti-apoptosis/cell death, and cellular response to unfolded proteins/topologically incorrect proteins, which is consistent with the SASP-induced apoptosis phenotype that we recently observed in KSHV + PEL cell-lines [2] , [3] . Therefore, our microarray data indicate that xCT as well as downstream controlled genes may represent new “drug targets” for better PEL treatment.…”
Section: Experimental Design Materials and Methodssupporting
confidence: 85%
“…Interestingly, our recent data showed that silencing of 1 DNA damage-related gene, XRCC5 (x-ray repair cross-complementing protein 5, also known as Ku80) enhanced the induction of apoptosis and programmed cell death by low-dose concentrations of DNA-damage reagents such as doxorubicin. 28 In fact, it has been reported recently that KSHV can activate the DNA damage response during de novo infection of primary endothelial cells and this plays a role in establishing latency. 51 More recently, it has been demonstrated that lytic reactivation of KSHV leads to activation of the ataxia telangiectasia mutated (ATM) and DNA-dependent protein kinase DNA damage response kinases.…”
Section: Discussionmentioning
confidence: 99%
“…Biotin-labeled RNA was generated using the TargetAmp-Nano Labeling kit for Illumina Expression BeadChip (Epicentre), according to the manufacturer's instructions, and hybridized to the HumanHT-12 v4 Expression BeadChip (Illumina). 27,28 The microarray experiments were performed twice for each group and the average values were used for analysis. Common, similar, and unique sets of genes and enrichment analysis were performed using MetaCore software (Thompson Reuters) as previously reported.…”
Section: 26mentioning
confidence: 99%
“…Apoptosis is a common form of programmed cell death that can be engaged via the intrinsic or extrinsic pathways. Recently, it has been shown that the glutamate cystine exchanger xCT (SLC7a11) appears to be essential in the process of chemo-resistance in some cancer cell types [ 8 , 9 ]. Hence, since xCT plays a pivotal role in tumor microenvironment interactions, i.e.…”
Section: Introductionmentioning
confidence: 99%